Mutational sources of trans-regulatory variation affecting gene expression in Saccharomyces cerevisiae - Duveau, Fabien; Vande Zande, Petra; Metzger, Brian PH; Diaz, Crisandra J; Walker, Elizabeth A; Tryban, Stephen; Siddiq, Mohammad A; Yang, Bing; Wittkopp, Patricia J (eLife, 2021)
Heritable variation in a gene’s expression arises from mutations impacting cis - and trans -acting components of its regulatory network. Here, we investigate how trans -regulatory mutations are distributed within the genome and within a gene regulatory network by identifying and characterizing 69 mutations with trans -regulatory effects on expression of the same focal gene in Saccharomyces cerevisiae . Relative to 1766 mutations without effects on expression of this focal gene, we found that these trans -regulatory mutations were enriched in coding sequences of transcription factors previously predicted to regulate expression of the focal gene. However, over 90% of the trans -regulatory mutations identified mapped to other types of genes involved in diverse biological processes including chromatin state, metabolism, and signal transduction. These data show how genetic changes in diverse types of genes can impact a gene’s expression in trans , revealing properties of trans -regulatory mutations that provide the raw material for trans -regulatory variation segregating within natural populations.